Balimau Tradition in the Wedding Procession in Nagari Koto Alam, Pangkalan Koto Baru District, Limapuluh Kota Regency, West Sumatra Province - Erlinda, Rilda Yunisa; Endrizal; Kahanna , Mutia (Kirana Publisher (KNPub), 2024)
This study examines the